Scorsese and Religion - Barnett, Christopher B.,; Elliston, Clark J., (Studies in Religion and the Arts ;, 2019)
Scorsese and Religion concerns the religious vision of the great American filmmaker Martin Scorsese. Not only will this volume explore the foundation of Scorsese's interest in religion-namely, his relation to the Catholic Church-but it will also highlight the religious breadth of Scorsese's corpus. Ultimately, this book demonstrates that Scorsese's cinematic "re-presentation" of reality brings together various religious influences (Catholicism, existentialism, Buddhism, etc.) and topics such as violence, morality, nihilism, and so on. The overarching claim is that Scorsese, who indeed once claimed that his "whole life" had been "movies and religion," cannot be properly understood without reflecting on the ways in which his religious interests are expressed in and through his art.